2002
DOI: 10.1034/j.1600-0579.2002.00253.x
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposures occurring in students in a UK dental school1

Abstract: To reduce the incidence of these exposures, more instruction and training may be required in the earlier clinical years and more chairside assistance. Improvements are required in the monitoring of post-screening for seroconversion after HBV immunization, and in the reporting of test results in the event of an exposure incident. Under-reporting of incidents is common and ways to encourage and facilitate reporting should be sought.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
61
2
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(77 citation statements)
references
References 10 publications
6
61
2
5
Order By: Relevance
“…Similarly, reported that there is no significant relationship between the gender of people, the use or nonuse of gloves and daytime, and occupational exposure. However, in the current study, occupational exposure in males was slightly higher than that in females [20]. In addition, in the study conducted by Utomi (2006), no significant relationship was found between exposure level of students and their age group, and no significant relationship was reported between the level of exposure and gender [19].…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Similarly, reported that there is no significant relationship between the gender of people, the use or nonuse of gloves and daytime, and occupational exposure. However, in the current study, occupational exposure in males was slightly higher than that in females [20]. In addition, in the study conducted by Utomi (2006), no significant relationship was found between exposure level of students and their age group, and no significant relationship was reported between the level of exposure and gender [19].…”
Section: Discussionmentioning
confidence: 77%
“…In a study conducted by Shaghaghian et al (2015), no significant relationship was found between the level of exposure and the demographic variables in dentistry students [21]. Stewardson et al (2004) also reported no significant relationship between age, gender, dominant hand, and time of day [22]. In another study conducted by Martins et al (2010), it was reported that occupational injuries were higher in female gender, older age, those consumed alcohol, single people, those who worked 8 h per day without resting, those who never used gloves, and those who always used the mask [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of viral hepatitis C particles in oral fluids has been demonstrated by many authors and this may indicate that transmission via saliva and gingival cervical fluid might occur [15,16]. Dentists and dental health care workers are at a high risk of infection with HCV during their daily occupational exposures [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, needlestick and similar injuries at medical 4,8,9) and dental educational institutions have been discussed in Japan [1][2][3]12) and other countries 5,6,10,11) , including England, Germany, and Australia.…”
Section: Introductionmentioning
confidence: 99%